Diet Quality Questionnaire, a tool for collecting food intake data to draw conclusions about diet quality - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
A visiting researcher at WUR, assisted by A4NH-supported students, led the development. It has been adapted for use in 90 countries. The Demographic and Healthy Survey in Uganda will use it in their next survey. In 2021, the Gallup World Poll incorporated the DQ-Q in 40 countries .